Pengaruh Corporate Social Responsibility dan Enterprise Risk Management Terhadap Nilai Perusahaan - Dylana Pricillia Anatasya; Dirvi Surya Abbas; Basuki Basuki (Journal Economic Excellence Ibnu Sina, 2023)
The purpose of this research is to determine the influence of corporate social responsibility and enterprise risk management on company value in various industrial sector companies listed on the Indonesia Stock Exchange. The research time period used was 4 years, namely the 2017-2020 period. The population of this research includes all companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 28 companies were obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 9.0 data processing program. The research results show that corporate social responsibility, enterprise risk management influence company value.